Tinjauan Remote Audit dan Skeptisisme Profesional Sebagai Penentu Kualitas Audit - Friska Amelia Putri; Ety Meikhati; Umi Hanifah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study is motivated by the ongoing digital transformation across various fields, including audit practices. The advancement of information technology has encouraged the adoption of various innovations, one of which is remote auditing, which allows audits to be conducted without direct face-to-face interaction with clients. At the same time, maintaining audit quality has become increasingly complex, requiring auditors to demonstrate a high level of professionalism, particularly in terms of professional skepticism. Auditor professionalism—including critical thinking skills, objectivity, and integrity—plays a crucial role in delivering high-quality audit outcomes. The objective of this study is to analyze the influence of remote auditing and professional skepticism on audit quality in external audit firms located in the Surakarta area. This research uses a quantitative approach with a case study design. Data were collected through questionnaires distributed to external auditors selected using purposive sampling, focusing on those with experience in conducting remote audits. The collected data were then analyzed using multiple linear regression to determine the influence of each independent variable on audit quality. The results indicate that, partially, professional skepticism has a significant effect on audit quality. This finding suggests that the higher an auditor's level of professional skepticism, the better the quality of the audit produced. In contrast, remote auditing does not show a significant partial influence on audit quality. However, when analyzed simultaneously, both variables—remote auditing and professional skepticism—have a significant effect on audit quality. In other words, while the use of audit technology is important, human factors remain the primary determinant of audit effectiveness. The implications of this study encourage audit firms not only to invest in digital audit systems but also to place greater emphasis on enhancing the competence and professionalism of auditors.